Chinese Asianism, 1894-1945 - Smith, Craig A. (Harvard University Asia Center E-Book Collection, Supplement 2021., 2022)
"Asianism was a "call" for Asian unity, Smith finds, but advocates of a united and connected Asia based on racial or civilizational commonalities also utilized the packaging of Asia for their own agendas, to the extent that efforts towards international regionalism spurred the construction of Chinese nationalism. Asianiam shaped Chinese ideas of nation and region, often by translating and interpreting Japanese perspectives, and leaving behind a legacy in the concepts and terms that persist in the twenty-first century. As China plays a central role in regional East Asian development, Asianism is once again of great importance today"--